Human Rights in Islam: A Comparative Analysis of Western and Islamic Perspectives and Their Application in Contemporary Society - Zulkifli (Islamic Studies and Education Journal, 2025)
Human Rights constitute a fundamental issue in contemporary global discourse and are predominantly understood through a Western secular-liberal framework. However, Islam offers a distinct conceptualization of human rights rooted in divine revelation and embedded within the framework of Islamic law (Sharia). This article aims to analyze the concept of human rights in Islam, compare it with the Western conception of human rights, and examine its relevance and application in contemporary society. This study employs a qualitative approach using library research, drawing upon primary sources such as the Qur’an, the Sunnah, the Medina Charter, and the Universal Declaration of Human Rights (UDHR) 1948, as well as relevant academic literature. Data are analyzed through descriptive-analytical and comparative methods, focusing on differences in normative sources, philosophical foundations, and value orientations. The findings reveal that Western human rights are largely anthropocentric and emphasize individual freedom in a relatively absolute manner, whereas Islamic human rights are theocentric, emphasizing a balance between rights and obligations grounded in the principles of monotheism, justice, and public welfare (maslahah). The article concludes that despite fundamental differences, Islamic human rights remain relevant and possess significant potential to be contextualized in modern society through a maqasid al-sharia approach.